Development of mango flavored Soy Dahi (Bangladesh Journal of Animal Science, 2013)
The experiment was aimed to prepare mango flavored soy milk based dahi (whole cow milk : soy milk=1:1). To remove the beany flavour of soybean as well as to add the mango flavour, mango juice were added at the rate of 0, 5, 10 and 15%. Data on physical and chemical parameters were recorded and analyzed. It was observed that smell and taste, body and consistency, color and appearance as well as total score were significantly increased (p